2019
DOI: 10.1002/aah.10089
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Acetylcholinesterase and Oxidative Stress Biomarkers in African Catfish Exposed to Carbendazim

Abstract: Carbendazim (CBZ) is a widely used, systemic, broad‐spectrum benzimidazole fungicide. It is used worldwide against fungal diseases on a wide range of agricultural products and in domestic gardens. The activities of brain oxidative stress biomarkers and acetylcholinesterase (AChE) in juvenile African Catfish Clarias gariepinus exposed to CBZ were investigated. Juveniles were exposed to sublethal concentrations of 0.22, 0.43, and 0.64 mg/L CBZ, which corresponded to 5, 10, and 15% of the 96‐h LC50 (the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…Interestingly, these data differ from other studies that report suppression in AChE induced by increased cellular oxidative stress (Flora et al, 2013; Kayode et al, 2016; Bali et al, 2019; Ezeoyili et al, 2019; Pala et al, 2019; Ibrahim et al, 2020). In general, such studies argue that this can occur due to the deterioration of neurotransmission and oxidative damage.…”
Section: Resultscontrasting
confidence: 89%
“…Interestingly, these data differ from other studies that report suppression in AChE induced by increased cellular oxidative stress (Flora et al, 2013; Kayode et al, 2016; Bali et al, 2019; Ezeoyili et al, 2019; Pala et al, 2019; Ibrahim et al, 2020). In general, such studies argue that this can occur due to the deterioration of neurotransmission and oxidative damage.…”
Section: Resultscontrasting
confidence: 89%
“…[ 7 ] The activity of acetylcholinesterase, an oxidative stress biomarker, was inhibited in the brain of the African cat fish Clarias gariepinus when exposed to sublethal concentrations of CBZ at 0.22–0.64 mg/L. [ 99 ] Thus, CBZ proves to be a strong oxidizing agent under in vitro‐vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fatty acids were down‐regulated in the LT‐28d samples, whereas, triglyceride was up‐regulated, suggesting triglyceride accumulation in the liver and subsequently an increase in intrahepatic lipids. Lipid alterations in fish have been associated with xenobiotic exposure, including carbendazim (Ezeoyili et al, 2019; Jiang et al, 2015; Rebelo et al, 2020; Sakr & Shalaby, 2014; Ziarrusta et al, 2018). A study carried out on adult zebrafish showed that carbendazim exposure affected glycolipid metabolism and detoxification metabolism in the liver (Bao et al, 2020).…”
Section: Resultsmentioning
confidence: 99%